CONTRASTIVE ANALYSIS OF WORD FORMATION OF A NEWSPAPER ARTICLE IN ENGLISH, UZBEK AND RUSSIAN LANGUAGES (American Journal of Pedagogical and Educational Research, 2023)
This article attempts to systematize the available theoretical material in the field of functional styles of the English language. The author of the article considers that functional styles are language subsystems, each of which has its own specific features in lexicon and phraseology, in syntactic constructions, and sometimes in phonetics. Occurrence and existence of functional styles is caused by specific conditions of communication in different spheres of human activity. Each style represents a system of closely connected lexical, grammatical and phonetic means. The name functional style is very successful, because the specificity of each style follows from the features of language functions in this area of communication. Thus, for example, the publicistic style has its main function of influencing the will, consciousness and feelings of the listener or reader, while the scientific style - only the transmission of intellectual content. The functional styles are well studied, and the differences in their distinction concern only the style of fiction prose and the single newspaper style.